Discoverers of Siberian oil and gas: from Raul-Yuri G. Ervier to Farman K. Salmanov. Sabit A. Orudzhev, Igor S. Gramberg and others — discoverers of gas and oil in the arctic shelf - V. L. Shuster (Известия высших учебных заведений: Геология и разведка)
The work perpetuates the names of scientists and discoverers of hydrocarbon deposits who have contributed to the development of the oil and gas industry. These figures are the finest examples of service to the Motherland, Society, and Science. The article is based on the results of a report at the plenary section of the international scientific conference entitled “Formation and development of the oil and gas industry — the contribution of Russian and Azerbaijani scientists and specialists”.